2006
DOI: 10.1183/09031936.00000106
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of systemic antioxidant profile in nonsmall cell lung carcinoma

Abstract: The present study aimed to determine the alterations of antioxidant activities in erythrocytes from patients with nonsmall cell lung carcinoma (NSCLC).A comparative study of the systemic antioxidant activities in red blood cell lysate from subjects with NSCLC and healthy control subjects was conducted. The antioxidants catalase, superoxide dismutase (SOD) and glutathione peroxidase (GPx) were measured using chemical kinetic reactions under spectrophotometry.In total, 189 cases of mostly advanced-stage IIIB or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
2
24
0
1
Order By: Relevance
“…Many studies have already reported that GPX1 may protect cancer cells under conditions of severe oxidative stress as it has been observed that increased GPX1 activity can inhibit apoptosis (14,15), reduce tumor sensitivity toward ROSgenerating anticancer drugs (17,18), and promote the more malignant stages of cancer (16). Our findings showed that SBP1 could greatly inhibit the activity, but not expression, of GPX1 in cancer cells both in vitro and in vivo; the translocation of GPX1 to the nucleus in cancer cells under oxidative stress may facilitate the antioxidant functions of GPX1, whereas the formation and combination of GPX1 and SBP1 nuclear bodies might inhibit this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have already reported that GPX1 may protect cancer cells under conditions of severe oxidative stress as it has been observed that increased GPX1 activity can inhibit apoptosis (14,15), reduce tumor sensitivity toward ROSgenerating anticancer drugs (17,18), and promote the more malignant stages of cancer (16). Our findings showed that SBP1 could greatly inhibit the activity, but not expression, of GPX1 in cancer cells both in vitro and in vivo; the translocation of GPX1 to the nucleus in cancer cells under oxidative stress may facilitate the antioxidant functions of GPX1, whereas the formation and combination of GPX1 and SBP1 nuclear bodies might inhibit this process.…”
Section: Discussionmentioning
confidence: 99%
“…GPX1 is a ubiquitously expressed antioxidant enzyme that scavenges organic hydroperoxides and protects cells from reactive oxygen species (ROS) and hydrogen peroxide-induced or -dependent apoptotic injury (14,15). Elevated GPX1 activity was reported to protect cancer cells from oxidative stress and anticancer agents (16)(17)(18). Previous studies using coimmunoprecipitation showed that these 2 distinct selenium-containing proteins (GPX1 and SBP1) can form a physical association that facilitates their interactions (19), but their possible roles in cancer development are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The serum levels of SOD, GPx and CAT and vitamin C and E were significantly declined in patients with multiple myeloma whereas malondialdehyde levels were elevated as compared with controls studied recently [45] . A comparative study of the systemic antioxidant activities in red blood cell lysate from subjects with non-small cell lung carcinoma (NSCLC) and healthy control subjects was conducted [46] . In this study, in subjects with lung cancer, there was similar CAT activity, lower SOD activity and higher GPx activity compared with controls.…”
Section: Expression Of All Antioxidant Enzymes Is Not Similar In Diffmentioning
confidence: 99%
“…These antioxidants can intercept, scavenge, and neutralize radicals and their reactive intermediates. The most significant antioxidant enzymes are superoxide dismutase (SOD), occurring in 3 isoforms, catalase (CAT), and glutathione peroxidase (GPX) [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are mainly situated intracellularly [13]. The term “oxidative stress” is defined as the adverse condition resulting from an imbalance between cellular oxidants (mostly ROS and RNS) and antioxidants (enzymatic, such as CAT and SOD, and others).…”
Section: Discussionmentioning
confidence: 99%